2008
DOI: 10.1177/1533210107313917
|View full text |Cite
|
Sign up to set email alerts
|

CAM Curriculum Activities to Enhance Professionalism Training in Medical Schools

Abstract: Enhancing the professionalism of graduates is a major objective of most health care education institutions today. Educating conventional health care providers about complementary and alternative medicine (CAM) may directly and indirectly improve trainee professionalism by expanding trainees' knowledge and appreciation of diverse health care beliefs and practices, improving physician-patient communication, enhancing self-care, and increasing sense of competence and job satisfaction. A survey based on profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
1
Order By: Relevance
“…Many of the graduates’ comments reflect how their self- and/or situational awareness improved their ability to care for patients. Indeed, previous work has linked physician well-being with professionalism(18) and suggested that CAM education may enhance professionalism and humanism by encouraging an openness to explore patient preferences and cultural views as well as use of self-care habits that may enhance self-awareness and reduce the effects of work-related stress and burnout(1921). …”
Section: Discussionmentioning
confidence: 99%
“…Many of the graduates’ comments reflect how their self- and/or situational awareness improved their ability to care for patients. Indeed, previous work has linked physician well-being with professionalism(18) and suggested that CAM education may enhance professionalism and humanism by encouraging an openness to explore patient preferences and cultural views as well as use of self-care habits that may enhance self-awareness and reduce the effects of work-related stress and burnout(1921). …”
Section: Discussionmentioning
confidence: 99%
“…Educating conventional health care providers about T&CM may directly or indirectly improve trainee professionalism by expanding trainees’ knowledge, appreciation of diverse health care benefits and medical practices, improving T&CM physician-to-patient communication, enhancing self-care, and increasing sense of competence and job satisfaction. 7 …”
mentioning
confidence: 99%
“…In particular, there are no national standards for certifying CAM practitioners or what qualifies as a specific therapy [1]. Similarly, the Consortium of Academic Health Centers for Integrative Medicine is seeking to create “a seamless integration of effective complementary and conventional approaches to promote healing and health in every individual and community [15]. ” This consortium is made up of 51 academic health centers and institutions with a common goal to share ideas, increase academia’ s curricula, research, and clinical care related to integrative medicine, and inform others on research that supports the use of integrative medicine [15].…”
Section: Discussionmentioning
confidence: 99%